Carbonic Anhydrase Inhibitors Featuring a Porphyrin Scaffold: Synthesis, Optical and Biological Properties. Issue 21 (15th February 2022) - Merabti, Amina; Roger, Maxime; Nguyen, Christophe; Nocentini, Alessio; Gerbier, Philippe; Richeter, Sébastien; Gary‐Bobo, Magali; Supuran, Claudiu T.; Clément, Sébastien; Winum, Jean‐Yves
Abstract: The synthesis, characterization and study of optical properties of innovative tetrafunctionalized zinc(II) porphyrins with carbonic anhydrase (CA) inhibitors in sulfonamide and coumarin series are described. The synthetic methodology relies on the preparation of the porphyrin core by condensation of azido triethyleneglycol functionalized benzaldehyde derivative with pyrrole followed by its metalation and inhibitors coupling via Huisgen click‐reaction. The tetrafunctionalized zinc(II) porphyrin with coumarin moieties showed selective inhibition against tumour‐associated hCA IX and hCA XII versus the cytosolic off‐targets hCA I and hCA II. This compound was able to accumulate on cell membrane and to impair pancreas cancer cells (Capan‐1) proliferation in normoxic conditions with LC50 of 4.5 μM. Moreover, its optical properties revealed efficient photosensitizing properties, leading to cancer cells death under light irradiation, making this compound a suitable candidate for photodynamic therapy. Abstract : A tetrafunctionalized zinc porphyrin with coumarin is able to accumulate on cell membrane by targeting selectively membrane‐bound tumour‐associated CA IX/CAXII, to impair pancreas cancer cell proliferation and to kill them by photodynamic therapy.